Current Update on Intrinsic and Acquired Colistin Resistance Mechanisms in Bacteria - Gogry, Firdoos Ahmad; Siddiqui, Mohammad Tahir; Sultan, Insha; Haq, Qazi Mohd. Rizwanul (Frontiers in Medicine, 2021)
Colistin regained global interest as a consequence of the rising prevalence of multidrug resistant Gram negative Enterobacteriaceae. In parallel, colistin resistant bacteria emerged in response to the unregulated use of this antibiotic. However, some Gram negative species are intrinsically resistant to colistin activity, such as Neisseria meningitides, Burkholderia spp, and Proteus mirabilis. Most identified colistin resistance usually involves modulation of lipid A that decreases or removes early charge based interaction with colistin through up-regulation of multi-step capsular polysaccharide expression. The membrane modifications occur by the addition of cationic phosphoethanolamine or 4-amino-L-arabinose on lipid A that results decrease in the negative charge on the bacterial surface. Therefore, electrostatic interaction between polycationic colistin and lipopolysaccharide is halted. It has been reported that these modifications on the bacterial surface occur due to overexpression of chromosomally mediated two component system genes (PmrAB and PhoPQ) and mutation in lipid A biosynthesis genes that result in lost of the ability to produce lipid A and consequently lipopolysaccharide chain.Thereafter, recently identified variants of plasmid borne genes (mcr-1 to mcr-10). It was hypothesized that mcr genes derived from intrinsically resistant environmental bacteria that carried chromosomal pmrC gene, a part of the pmrCAB operon codes three proteins viz. phosphoethanolamine (pEtN) response regulator PmrA,sensor kinase protein PmrAB and phosphotransferase PmrC.These plasmid borne mcr genes become a serious concern as they assist in the dissemination of colistin resistance to other pathogenic bacteria.This review presents the progress of multiple strategies of colistin resistance mechanisms in bacteria, mainly focusing on surface changes of the outer membrane LPS structure and other resistance genetic determinants.New handier and versatile methods have been discussed for rapid detection of colistin resistance determinants and the latest approaches to revert colistin resistance that include the use of new drugs,drug combinations and inhibitors.Indeed, more investigations are required to identify the exact role of different colistin resistance determinants that will aid in developing new less toxic and potent drugs to treat bacterial infections.Therefore, colistin resistance should be considered a severe medical issue requiring multi sectoral research with proper surveillance and suitable monitoring systems to report the dissemination rate of these resistant genes.